Cidade tombada, territórios tomados: sobre-vivências e r-existências a partir do rompimento da barragem de rejeitos de minério do Fundão, em Mariana, Minas Gerais - Flora d'El Rei Lopes Passos (2019)
In a same city, many cities coexist. A heritage city integrates taken territories, sometimes by economic interests, reflecting domination processes, sometimes by social groups that appropriate spaces in daily life. Recognizing this dialectical relationship between domination and appropriation in cities and territories is the main goal of this research. Most of the time, it is possible to notice that domination established in the territories materialize in urban renovation projects, which intend to create consensual and visible scenarios. However, there are other forms of domination, especially in small and medium-sized cities of the state of Minas Gerais, Brazil, which are related to large mining enterprises that define areas of exploration interest, turning them into strategically invisible territories. At the same time, social practices of daily appropriation of territories can be apprehended as experiences of social exchange and tools of struggling for justice in cities. What is the force field established from the intertwining of culture and territory in heritage cities? To what extent are relations of domination engendered in territories and evidenced in situations of conflict? How to recognize the experiences, permanencies, existences and resistances that contradict the hegemonic order and suggest the struggle for rights and social justice in cities? The municipality of Mariana, in the state of Minas Gerais, Brazil, is presented as a case study in this research, as it is considered a heritage city and is exploited by mining, having become the scene of an unprecedented socio-environmental disaster in Brazil and in the world: the disruption of the ore tailings dam called Fundão, under the responsibility of Samarco/Vale/BHP Billiton companies, in November 5th 2015. The methodological paths taken in this research include bibliographic and journalistic research; semi-structured interviews with local institutional actors; open interviews with affected Mariana’s residents; besides participant observation in meetings, public hearings and traditional festivities organized by the residents in the affected territories. The research showed an asymmetrical force field, where the companies responsible for the disaster-crime and for the reparation and compensation of damages maintained the domination and continuous violation of rights, including the right to the appropriation of the affected territories. Dialectically, everyday social practices in these territories can be apprehended as experiences of social exchange, conflict and dissent and as instruments of struggle and resistance. Popular festivities organized by the residents, provided the gathering of people in common spaces and, therefore, the appropriation, reaffirming the sense of belonging and the desire for the reestablishment of the destroyed ways of life. Experiences and re-existences are those that allow the construction of counterhegemonic processes in the cities, contrarily to the dominant order.